Mobile Learning Media for Computer and Based Network at Vocational High School - Mayefis, Reska (International Journal of Natural Science and Engineering, 2022)
Currently, there are still many students who like digital-based learning activities. This study aims to analyze the need for developing Android-based mobile learning media in SMK. The type of research used is survey research and literature study. The methods used in collecting data are observation, interviews, and questionnaires. The instruments used are interview sheets and questionnaires. The data analysis technique used is descriptive statistics. The study results showed that around eighty-two percent of students actively use smartphones outside learning hours. Students who use smartphones in learning are more informal, using them more to find information. On the other hand, only twenty-five students use smartphones to access course materials. Students agree to use their smartphones to study in class because it can increase their interest in learning and their ability to understand the subject matter better. Learning media can be a source of learning for students and help teachers in teaching, and learning activities can be more effective.